2020
DOI: 10.1088/1755-1315/553/1/012004
|View full text |Cite
|
Sign up to set email alerts
|

First report of the parasitoid wasp Platygaster oebalus (Hymenoptera: Platygastridae) from Iraq

Abstract: The parasitoid wasp Platygaster oebalus was collected from Karbala city in April 2019 and recorded for the first time from Iraq.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Some species of Platygastroidea were reported by Kononova & Kozlov (2008) from Turkey. Three species of Scelio Latreille, 1805 (Hymenoptera: Platygastroidea: Scelionidae) (Polaszek et al 2019) and Platygaster oebalus Walker, 1835 (Hymenoptera: Platygastridae) (Kareem et al 2020) have been reported from Iraq. A new genus and species of platygastrid flies, namely Psix abnormis Kozlov & Le, 1976, were described from Afghanistan (Kozlov & Le 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Some species of Platygastroidea were reported by Kononova & Kozlov (2008) from Turkey. Three species of Scelio Latreille, 1805 (Hymenoptera: Platygastroidea: Scelionidae) (Polaszek et al 2019) and Platygaster oebalus Walker, 1835 (Hymenoptera: Platygastridae) (Kareem et al 2020) have been reported from Iraq. A new genus and species of platygastrid flies, namely Psix abnormis Kozlov & Le, 1976, were described from Afghanistan (Kozlov & Le 1976).…”
Section: Discussionmentioning
confidence: 99%